Association between intra-operative hemodynamic changes and corrective procedures during posterior spinal fusion in adolescent patients with scoliosis: A case-control study. Issue 52 (30th December 2021) - Wada, Kanichiro; Kumagai, Gentaro; Kudo, Hitoshi; Tanaka, Sunao; Asari, Toru; Fjita, Yuki; Ishibashi, Yasuyuki
Abstract : Abstract: Previous reports indicated that a decrease in intra-operative cardiac output and mean arterial pressure occurs due to thoracic cage deformities when patients with scoliosis are placed in the prone position. The aims of this study were to investigate the occurrence of hypotension during posterior spinal fusion in adolescent patients with scoliosis, and the association between hypotension, surgical procedures, changes of thoracic cage morphology. This retrospective, single-center, case-control study included 106 patients who underwent surgeries for spinal deformity at our institute between June 2014 and March 2020. The inclusion criteria were: age ≤19 years at the time of surgery, lowest instrumented vertebra over L5, posterior spinal fusion as the first surgery for scoliosis, and no severe cardiac or pulmonary disease pre-operatively. Finally, 49 patients met the criteria, and were divided to 3 groups as follows: thoracic constructive curve using a 6.0-mm cobalt-chromium alloy circular rod (T-C group; n = 28); thoracolumbar/lumbar constructive curve using a 6.0-mm cobalt-chromium alloy circular rod (L-C group; n = 8); and thoracic constructive curve using a 5.5-mm cobalt-chromium alloy beam-like rod (T-B group; n = 13). The beam-like rod is characteristic as the rod is mounted to screw heads without cantilever force. Intra-operative changes in circulation associated with corrective procedures, perioperative data, and sagittal depth and sternum deviation of thoracic cage were compared between the 3 groups. The T-C group had a higher rate of hypotension alarm than did the other groups (7 vs 0 vs 0; P  = .047). Corrective procedures included rodding 4 times, rod rotation maneuver once, and direct vertebral rotation twice. Blood pressure was increased by pausing the correction procedures, increasing infusion, and administering vasopressors. The T-C and T-B groups had greater sternum deviation parameters than the L-C group, both before and after surgery. All parameters associated with sagittal depth and sternum deviation decreased significantly after surgery in the T-C and the T-B groups. In corrective surgery for constructive thoracic scoliosis, the corrective procedures requiring the application of compression force in the forward direction should be closely monitored in view of their possible influence on circulatory conditions.